Building A Value-Based Workforce: Human Resources Management Models For Recruitment In Pesantren - Akmal Mundiri; Eny Zakiyah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
The recruitment of teaching staff in Islamic boarding schools is a phenomenon that has unique characteristics and differs from recruitment practices in general educational institutions. This study aims to examine pesantren-based recruitment management at Pondok Pesantren Nurul Jadid, particularly in integrating academic competence with pesantren values and traditions. This study uses a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation. The results show that the recruitment process at Pondok Pesantren Nurul Jadid has a crucial characteristic, namely, it begins with the identification of human resource needs tailored to the activities of the Islamic boarding school, followed by a multi-stage selection process that emphasizes mastery of furudul ainiyah and the Qur'an. The final decision-making process involves the central role of the kiai and pesantren leaders, as well as considering family approval as a form of moral accountability. Recruitment is also integrated with orientation and tiered training programs, such as Student Care Management (MPS), guardianship training, and management training, as a means of internalizing pesantren values. This study confirms that pesantren-based recruitment is a holistic value-based system that functions strategically in maintaining the identity of pesantren while improving the quality of education.